Evaluating the Short-Term Outcome of Mechanically Ventilated Neonates Admitted to the Neonatal Intensive Care Unit of Besat Hospital, Hamadan, Iran - Amir Reza Monsef (International Journal of Pediatrics, 2019)
Background Many neonates admitted to Neonatal Intensive Care Unit (NICU) need mechanical ventilation for recovery. This study was designed to evaluate the short-term outcome of mechanically ventilated neonates admitted to NICU. Materials and Methods In this descriptive cross-sectional study, all the neonates in need of mechanical ventilation in NICU of Besat Hospital, Hamadan, Iran, were enrolled for one year from September 2017 to September 2018. The selected data were of neonatal age at admission time, birth weight, gender, gestational age, indications of mechanical ventilation, lab results, length of hospital stay and the outcome of the disease were extracted from the medical file and analyzed using SPSS software (version 22.0). Results Of 141 mechanically ventilated neonates, 55.3% (n=78) were males. The mean of neonatal age, mean gestational age and mean birth weight were, 4.67 ± 6.58 days, 35.51 ± 3.88 weeks, and 2779.37 ± 827.06 g, respectively. RDS (58.9%) was the most common indication for mechanical ventilation. The overall rate of neonatal recovery was 51.8%. The results of unilabiate analysis showed a significant relationship between indications of mechanical ventilation, gestational age, neonatal birth weight, acidosis (pH <7.1), duration of mechanical ventilation, duration of hospitalization and the disease outcomes (P<0.05). Conclusion The results of this study showed that respiratory distress syndrome, low gestational age and birth weight, acidosis and duration of mechanical ventilation would lead to increased death in mechanically ventilated neonates.